Expert Answers
Matthew Fonda eNotes educator| Certified Educator

The key here is to remember the rule for dividing with exponents:

`x^a / x^b = x^(a-b)`

Applying this rule here, we find:

`a^7/a^4 = a^(7-4) = a^3`

Another way of solving this problem is by remembering that a number raised to an exponent is the number multiplied by itself that many times:

`a^7 / a^4 =(a*a*a*a*a*a*a) / (a*a*a*a) = a*a*a = a^3`

Access hundreds of thousands of answers with a free trial.

Start Free Trial
Ask a Question